Mental Fatigue and Functional Near-Infrared Spectroscopy (fNIRS) – Based Assessment of Cognitive Performance After Mild Traumatic Brain Injury - Skau, Simon; Bunketorp-Käll, Lina; Kuhn, Hans Georg; Johansson, Birgitta (Frontiers in Human Neuroscience, 2019)
Pathological mental fatigue after mild traumatic brain injury (TBI-MF) is characterized by pronounced mental fatigue after cognitive activity. The neurological origin is unknown, and we aimed in the present study to investigate how prolonged mental activity affects cognitive performance and its neural correlates in individuals with TBI-MF. We recruited individuals with TBI-MF (n=20) at least 5 months after injury, and age-matched healthy controls (n=20). We used functional near-infrared spectroscopy (fNIRS) to assess hemodynamic changes in the frontal cortex. The self-assessed mental energy level was measured with a visual analog scale before and after the experimental procedure. A battery of six neuropsychological tests including Stroop-Simon, Symbol Search, Digit Span, Parallel Serial Mental Operation, Sustained Attention and Working Memory test, and Digit Symbol Coding were used. The sequence was repeated once after an eight-minute sustained-attention test. The test procedure lasted 2 ½ hours. The experimental procedure resulted in a decrease in mental energy in the TBI-MF group, compared to controls (interaction, p<0.001, ηp2 = 0.331). The TBI-MF group performed at a similar level on both Digit Symbol Coding tests, whereas the controls improved their performance in the second session (interaction, p<0.01, ηp2 = 0.268). During the Stroop-Simon test, the fNIRS event-related response showed no time effect. However, the TBI-MF group exhibited lower oxygenated hemoglobin (oxy-Hb) concentrations in the frontal polar area, ventrolateral motor cortex and dorsolateral prefrontal cortex from the beginning of the test session. A Stroop and Group interaction was found in the left ventrolateral prefrontal cortex showing that the TBI-MF group did have the same oxy-Hb concentration for both congruent and incongruent trials, whereas the controls had more oxy-Hb in the incongruent trial compared to the congruent trial (interaction, p<0.01, ηp2 = 0.227). In sum these results indicate that individuals with TBI-MF have a reduced ability to recruit the frontal cortex, which is correlated with self-reported mental fatigue. This may result both in deterioration of cognitive function and the experience of a mental fatigue after extended mental activity.